Molecular interactions between the specialist herbivore Manduca sexta (Lepidoptera, Sphingidae) and its natural host Nicotiana attenuata. VII. changes in the plant's proteome - Giri, Ashok P.; Wuensche, Hendrik; Mitra, Sirsha Sribas; Zavala, Jorge A.; Muck, Alexander; Svatos, Ales; Baldwin, Ian T. (Plant Physiology, 2006)
When Manduca sexta attacks Nicotiana attenuata, fatty acid-amino acid conjugates (FACs) in the larvae's oral secretions (OS) are introduced into feeding wounds. These FACs trigger a transcriptional response that is similar to the response induced by insect damage. Using two-dimensional gel electrophoresis, matrix-assisted laser desorption ionization-time of flight, and liquid chromatography-tandem mass spectrometry, we characterized the proteins in phenolic extracts and in a nuclear fraction of leaves elicited by larval attack, and/or in leaves wounded and treated with OS, FAC-free OS, and synthetic FACs. Phenolic extracts yielded approximately 600 protein spots, many of which were altered by elicitation, whereas nuclear protein fractions yielded approximately 100 spots, most of which were unchanged by elicitation. Reproducible elicitor-induced changes in 90 spots were characterized. In general, proteins that increased were involved in primary metabolism, defense, and transcriptional and translational regulation; those that decreased were involved in photosynthesis. Like the transcriptional defense responses, proteomic changes were strongly elicited by the FACs in OS. A semiquantitative reverse transcription-PCR approach based on peptide sequences was used to compare transcript and protein accumulation patterns for 17 candidate proteins. In six cases the patterns of elicited transcript accumulation were consistent with those of elicited protein accumulation. Functional analysis of one of the identified proteins involved in photosynthesis, RuBPCase activase, was accomplished by virus-induced gene silencing. Plants with decreased levels of RuBPCase activase protein had reduced photosynthetic rates and RuBPCase activity, and less biomass, responses consistent with those of herbivore-attacked plants. We conclude that the response of the plant's proteome to herbivore elicitation is complex, and integrated transcriptome-proteome-metabolome analysis is required to fully understand this ubiquitous ecological interaction.

Genetic diversity analysis of mango cultivars using inter simple sequence repeat markers - Pandit, Sagar S.; Mitra, Sirsha Sribas; Giri, Ashok P.; Pujari, Keshav H.; Patil, Bhimarao P.; Jambhale, Narayan D.; Gupta, Vidya S. (Current Science, 2007)
With 33 polymorphic Inter Simple Sequence Repeat (ISSR) markers, genetic diversity among 70 mango cultivars and a distant outgroup was analysed. Clustering was done using Dice and Jaccard coefficients with bootstrapping. Multivariate analysis was conducted using the Euclidean distances. Among the total 420 bands, 408 were polymorphic. Probability that any ISSR fragment is shared by two different cultivars was calculated to be 2.54 x 10(-1). Non-Indian mango cultivars were found genetically diverged from Indian mango germ pool. No separation was observed between North Indian and South Indian cultivars. Twelve different cultivar-specific bands were detected for six cultivars, which approved the effectiveness of ISSR markers in mango genetic diversity analysis.
Keywords: DNA finger printing; inter simple sequence repeat; Mangifera indica; principle coordinate analysis

Quick method for isolating RNA from raw and ripe fleshy fruits as well as for co-isolating DNA and RNA from polysaccharide- and polyphenol-rich leaf tissues - Pandit, Sagar Subhash; Mitra, Sirsha Sribas; Giri, Ashok P.; Gupta, Vidya Shrikant (Journal of Plant Biology, 2007)
Qualitative and quantitative changes in its chemical composition make it difficult to use any single procedure for isolating good-quality RNA from fruits at various ripening stages. Although the CTAB method has eliminated some specific problems, e.g., low pH in raw fruit or high levels of polysaccharides, oligosaccharides and phenolics in raw and ripe fruits, the total time required is long and unsuitable for high throughput. Here, we successfully modified this CTAB protocol to isolate good-quality RNA from (i) fleshy fruits, especially raw and ripe mangos; (ii) the leaves of a succulent air plant; and (iii) an oligosaccharide-rich onion epidermis. This RNA proved useful for downstream transcriptomic applications, where RT-PCR followed by RACE yielded the complete open reading frame of the (mango) terpene synthase gene. We also extended the utility of this protocol to co-isolate good-quality genomic DNA from the supernatant that remained after RNA precipitation. This preparation was useful for the arbitrary primer multilocus amplification of genomic DNA as well as for single locus diversity marker amplifications of the ctDNA and mtDNA.
Keywords: DNA-RNA co-isolation; fleshy fruit; Mango; oligosaccharide-rich; Ripening; transcriptomic studies